The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1200/po.21.00543
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Features of Lung-Recurrent Hormone-Sensitive Prostate Cancer

Abstract: PURPOSE Pulmonary involvement is rare in metastatic hormone-sensitive prostate cancer (mHSPC) that recurs after treatment for localized disease. Guidelines recommend intensive systemic therapy, similar to patients with liver metastases, but some lung-recurrent mHSPC may have good outcomes. Genomic features of lung metastases may clarify disease aggression, but are poorly understood since lung biopsy is rarely performed. We present a comparative assessment of genomic drivers and heterogeneity in metachronous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…14,15,16 Additionally, studies have shown that underlying biology could be more important analysis is muddled by the aggregation of "visceral" disease even though the biology and prognosis of these sites may differ depending on sites of metastasis. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,16 Additionally, studies have shown that underlying biology could be more important analysis is muddled by the aggregation of "visceral" disease even though the biology and prognosis of these sites may differ depending on sites of metastasis. 19…”
Section: Discussionmentioning
confidence: 99%
“…Missing information on some variables such as tumor stage or M‐Stage at presentation should be noted. Further, our analysis is muddled by the aggregation of “visceral” disease even though the biology and prognosis of these sites may differ depending on sites of metastasis 19 …”
Section: Discussionmentioning
confidence: 99%
“…Fonseca et al. reported the results of an analysis of 10 cases of metastatic castration‐sensitive prostate cancer that recurred after radical treatment, in which biopsy or resection of the lung metastases was performed 10 . They found that recurrent lung metastases did not contain the deleterious mutations in TP53 and DNA damage‐repair genes that characterize aggressive cancer, and that copy number changes and clonal mutations were highly conserved between metastases and primary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca et al reported the results of an analysis of 10 cases of metastatic castration-sensitive prostate cancer that recurred after radical treatment, in which biopsy or resection of the lung metastases was performed. 10 They found that recurrent lung metastases did not contain the deleterious mutations in TP53 and DNA damage-repair genes that characterize aggressive cancer, and that copy number changes and clonal mutations were highly conserved between metastases and primary lesions. This report suggests that selected metastatic castration-sensitive prostate cancer with recurrence in the lung may have different biological features than metastatic cancers with aggressive features, although these patients were carefully selected based on their clinical course and underwent biopsy or resection for lung metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the genomic features of lung metastasis were poorly explored in the literature apart from two case series that investigated the genomics of lung metastasis on metastatic hormone sensitive PCa (mHSPC) patients [56,60]. Shenderoev et al identified 16 mHSPC patients with plenty of variations in mismatch repair (MMR) genes, homologous recombination deficit (HRD) genes, PI3K pathway genes, Wnt signaling pathway genes, and TP53 mutations [56].…”
Section: Molecular and Geneticsmentioning
confidence: 99%